Cognitive Construction of Humor through Modal-World Negotiation: A Text World Theory Analysis of Multimodal Narrative in Air Buddies - Agnes Caroline Baene; Rohani Ganie; Rahmadsyah Rangkuti; Umar Mono; Syahron Lubis (Universitas Pendidikan Ganesha, 2026)
Research on humor in films is still predominantly dominated by pragmatic and cultural perspectives, thus providing limited explanation of how comedic effects emerge through structured cognitive processes in multimodal children’s films. This gap indicates a lack of integrative analysis that connects humor construction with narrative world-building mechanisms. This study aims to analyze the cognitive construction of humor in Air Buddies through the framework of Text World Theory. This study employs a qualitative interpretative design within the domain of Cognitive Stylistics. The research subjects consist of 30 dialogue excerpts selected purposively based on the presence of comedic elements and world-building indicators. Data were collected through documentation and non-participant observation using an analytical coding sheet as the research instrument. The instrument includes indicators of humor types, world-building components, and modal expressions. Data analysis was conducted through stages of humor classification, text-world mapping, modal-world analysis, and interpretative synthesis. The findings reveal that witty humor is the most dominant element, followed by parody, sarcasm, and playful humor, which function as cognitive triggers in modal-world shifts. The conclusion of this study shows that humor is cognitively constructed through layered world-building processes, thereby addressing the gap in understanding humor that has been limited to linguistic aspects. The implications of this study emphasize the importance of integrating cognitive stylistics and Text World Theory as a comprehensive framework for analyzing humor in multimodal narratives.